Shopping for a better country : essays - Novaković, Josip; Novakovich, Josip (Westland, MI : Dzanc Books, 2012)
A collection of narrative essays on family, history and travel from the Croatian-American author.
Shopping for a better country -- Dead fathers society -- Terrible twos travel -- Ruth's death -- On raising a prodigy -- Five easy pieces In Moscow -- Sumka 43, a captive cello -- Blue note -- The art of coughing -- On sleeping -- Friendship addiction -- Carthage, Algiers and Fes -- My Hungary -- Vukovar -- Two Croatias -- Berlin journal -- Why I can't write erotica -- Literary tombs -- Balkan express.
Keywords: Novakovich, Josip, -- 1956- -- Travel; Novakovich, Josip